2021
DOI: 10.21608/assjm.2021.187923
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chlorpyrifos and Bacillus Thuranginsis Israelinsis against Culex Pipiens (L.)

Abstract: https://assjm.journals.ekb.eg Efficacy of Chlorpyrifos and Bacillus Thuranginsis Israelinsis against Culex Pipiens (L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Halawa and colleagues 2021 on the effectiveness of chlorpyrifos and Bacillus thuranginsis israelinsis against Culex pipiens, the researchers found an increase in the value of AST enzyme in the tissue extract of the treated insects (43). Also, Sugeçti and Büyükgüzel reported that 1.5% of the oxfendazole compound caused oxidative stress in G. mellonella insect larvae, which was inferred by an increase in the level of AST enzyme in the treated insect's hemolymph (44).…”
Section: Aedes Aegypti Larvaementioning
confidence: 99%
“…Halawa and colleagues 2021 on the effectiveness of chlorpyrifos and Bacillus thuranginsis israelinsis against Culex pipiens, the researchers found an increase in the value of AST enzyme in the tissue extract of the treated insects (43). Also, Sugeçti and Büyükgüzel reported that 1.5% of the oxfendazole compound caused oxidative stress in G. mellonella insect larvae, which was inferred by an increase in the level of AST enzyme in the treated insect's hemolymph (44).…”
Section: Aedes Aegypti Larvaementioning
confidence: 99%